The Influence of Good Corporate Governance and ESG on Firm Value with Financial Performance as Moderator in IDX Energy and Mining - Diah Bayu Ramadhani Lubis; Erlina Erlina; Ibnu Austrindanney Sina Azhar (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study examines differences in firm value between the mining and energy sectors and investigates the impact of Environmental, Social, and Governance (ESG) and Good Corporate Governance (GCG) on firm value, with financial performance as a moderating variable. The sample consists of 24 mining and energy companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, resulting in 72 observations selected through purposive sampling. Data analysis used EViews and SPSS software applying multiple linear regression with panel data, Moderated Regression Analysis (MRA), and independent sample t-tests. Findings reveal that ESG negatively and significantly affects firm value, while GCG shows no significant impact. Financial performance does not moderate the relationships between ESG or GCG and firm value. The independent sample t-test shows no significant difference in firm value between the two sectors during the study period. These results suggest investors prioritize market conditions and financial fundamentals over non-financial disclosures, as governance and sustainability initiatives are yet to strongly influence firm value in these industries. The study contributes to corporate sustainability literature by emphasizing the limited role of ESG and governance in capital-intensive, regulated sectors, recommending future research to explore longer periods and additional moderating variables. Keywords: Good Corporate Governance; Environmental Social and Governance; Firm Value; Financial Performance